Speech Impact in Political Discourse in Context of COVID-19 Pandemic (Speeches of B. Johnson and D. Biden) - N. S. Dankova; E. V. Krekhtunova (Научный диалог)
The article is devoted to the study of pragmalinguistic means of political discourse. The material was transcriptions of speeches by British Prime Minister B. Johnson and US President D. Biden, published on the official websites of the governments of Great Britain and the United States. The authors set themselves the task of studying communication tactics that update the main directions of policy regarding COVID-19. The relevance of the work is due to the constructivist approach to the language. Political discourse is one of the ways to actualize power and control in society. The analysis revealed two groups of tactics that affect social consciousness and behavior: tactics of negative representation and tactics of positive representation. The tactics of negative representation of the pandemic include the following: emphasizing the threat, modeling a negative scenario, attracting negative experience. Positive representations are created through the use of tactics such as highlighting achievements, modeling a positive scenario, solidarity, appeals to duty, persuasion and appeal. It is shown that the linguistic means of updating the identified tactics have a targeted impact on the emotional sphere and on the consciousness of citizens, being a strong argument in favor of vaccination. The analysis carried out contributes to the understanding of the discursive mechanisms of influence on the mass consciousness.